Emerging Antibiotic Resistance Pattern in a Neonatal Intensive Care Unit in Pokhara, Nepal - Bastola, Ramchandra; Shrestha, Shree Krishna; Paudel, Rajan; Gurung, Laxmi; sigdel, Bhawana; Neupane, Jamuna; Pradhan, Saugat; Basnet, Omkar; Subedi, Nuwadatta (Journal of Nepal Health Research Council, 2025)
Background: Treating neonatal sepsis in Nepal remains difficult given the high rates of antimicrobial resistance. The objective of this study is to determine the antibiotic resistance pattern of culture-proven infections in neonates admitted to a neonatal intensive care unit. Methods: This cross-sectional prospective observational study was performed at the Neonatal Intensive Care Unit of Pokhara Academy of Health Sciences from 15th july 2022 to 15th july 2023. We included all neonates admitted with positive cultures grown from blood, cerebrospinal fluid, endotracheal tube, and pus. Demographic, clinical, and microbiologic data were collected from the medical record. We reviewed antimicrobial susceptibility testing of all isolates. Results: There were 51 culture-positive infections among 1327 neonates admitted, among which 23 cases from blood culture, 2 cases from cerebrospinal fluid, 14 cases from endotracheal tube samples, and 12 cases from pus samples. Gram-negative infections were predominant amounting to 35 (68.6%) including Pseudomonas in 12 (23.5%), and Acinetobacter species in 9 (17.6%) cases. Gram-positive infections were seen in 14 (27.4%) in which Methicillin-Resistant Staphylococcus aureus accounted for 6 (11.8%) cases. Yeast cells other than Candida albicans accounted for two (5.4%). For all Gram-negative isolates, resistance to Third-generation cephalosporin and aminoglycosides was reported in 75.0% (12 of 16 isolates tested) and 87.0% (24/31), respectively. Fluoroquinolone resistance was seen in 61% (8/13), resistance to penicillin was 59.3% (10/19), and resistance to carbapenem was in 100.0% (7/7) cases. Conclusions: There were high rates of antimicrobial resistance even with the reserved drugs among gram-negative pathogens. This alarms for the need for rationale prescribing of antimicrobials. Keywords: Antimicrobial resistance; bloodstream infection; meningitis, neonatal sepsis